Variable‐rate staircase codes with RS component codes for optical wireless transmission. Issue 4 (19th May 2016) - Kukieattikool, Pratana; Goertz, Norbert
Abstract: We investigate staircase codes, a class of high‐performance forward‐error‐correction codes for high‐rate transmission, and propose staircase codes with adaptive rates for time‐variant optical wireless channels. The variable‐rate staircase codes are used in a type‐II hybrid automatic repeat request framework such that throughput is maximised by avoiding retransmissions of the whole staircase blocks that initially—at high code rate—may not have been decoded successfully. These rate‐adaptive staircase codes employ at their core the standard Bose–Chaudhuri–Hochquenghem component codes, but they are concatenated with Reed–Solomon codes as extra components to implement burst‐error correction and rate‐adaptivity. Bit error performance and throughput of the rate‐adaptive staircase codes are investigated by analysis and confirmed with simulation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents a rate‐adaptive staircase code and application thereof in type‐II hybrid automatic repeat request for use on time‐varying optical wireless channels. This rate‐adaptive staircase code has Reed–Solomon codes as component codes to assist Bose–Chaudhuri–Hochquenghem core codes used on the standard staircase scheme. The performance and throughput simulations of this code reveal better performance on a wide range of input error probabilities.